2018
DOI: 10.1090/proc/14029
|View full text |Cite
|
Sign up to set email alerts
|

Arcwise connectedness of the set of ergodic measures of hereditary shifts

Abstract: We show that the set of ergodic invariant measures of a shift space with a safe symbol (this includes all hereditary shifts) is arcwise connected when endowed with the d-bar metric. As a consequence the set of ergodic measures of such a shift is also arcwise connected in the weak-star topology and the entropy function over this set attains all values in the interval between zero and the topological entropy of the shift (inclusive). The latter result is motivated by a conjecture of A. Katok.A shift space X over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Lemma 3.4 implies that E ′ := {z(y 1 , · · · , y n ) : (y 1 , · · · , y n ) ∈ E(v 1 , · · · , v n−1 )} is an (n(N + τ ), γ)-separated set in Y . By (14) and (12), we have (6) and (7), we have…”
Section: 2mentioning
confidence: 99%
“…Lemma 3.4 implies that E ′ := {z(y 1 , · · · , y n ) : (y 1 , · · · , y n ) ∈ E(v 1 , · · · , v n−1 )} is an (n(N + τ ), γ)-separated set in Y . By (14) and (12), we have (6) and (7), we have…”
Section: 2mentioning
confidence: 99%
“…both of which clearly follow from (15). Therefore, we know that G ′ has the threefold concatenatability property from Theorem 5.8.…”
Section: R Pavlovmentioning
confidence: 61%
“…A useful property of bounded density shifts is that they are hereditary (defined in [14]), meaning that whenever a letter in a point in the shift is replaced by a smaller letter, the resulting point is still in the shift. Hereditary shifts are known to have many useful properties (see [9,[15][16][17]) and so it is not surprising that they often have unique MME. However, signed bounded density shifts have no obvious hereditary properties.…”
Section: When H Is a Constant Function A ±mentioning
confidence: 99%
“…However, this is no longer true for a general (not necessarily B-free) hereditary system. On the other hand, Konieczny, Kupsa and Kwietniak [109] showed that the set of ergodic invariant measures of a hereditary shift is always arcwise connected (when endowed with the d-bar metric).…”
Section: Invariant Measures and Entropymentioning
confidence: 99%